Implementasi Sistem Informasi Pemesanan Tour Dan Travel - Anggoro, Wahyu; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2024)
Chaansa Travel is a travel agency service from Muaro Jambi engaged in selling Tour and Travel tickets. They operate the tickets manually where they use a large agenda book also not ready to utilize a computer. Customers order tickets by telephone and have to visit the office to get the tickets that have been ordered. This can trigger ordering time constraints if many orders received from various customers, resulting they must wait in line while what if the office location is far from the customer's position. Therefore, a new computerized system is required where customers order tickets by looking directly at available routes from the application. The purpose of this research is designing an Android-based Tour and Travel booking information system application. Hopefully, this can facilitate travel bookings, such accessing applications with online using smartphone, thereby avoiding queues for visits and facilitate travel agency to collect booking data easier. The application development methodology the author uses is the waterfall method. The result of this study is application designed using Android Studio with Kotlin also MySQL as database storage and it can be implemented using black box testing where the functionality of input and output app features can work well.